Metodologia procesualizacji zarządzania - między efektywnością a elastycznością - Cieśliński, Wojciech (Methodology of processualization of management - between flexibility and efficiency, 2006)
In the paper the author describes new directions for enterprise management. He presents methodology of proccssualization on the background of transformation in Polish enterprises. The proccssualization of management is a transitional period of changes in functioning of enterprises. The methods used in this area help, firstly, to "unfreeze” the structures, secondly they are the essential ingredient for further development of an enterprise towards more flexible economic networks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 86-92